Race and Mental Health in Higher Education: A systematic review (Research, Society and Development, 2021)
Objective: To present the results of a systematic review of the scientific literature that deals with how race/skin color stigmas influence the mental health of black university students. Methodology: The search was carried out in SciELO, Lilacs and PubMed databases; the descriptors used were: “mental health”, “students” and “race”, in the SciELO and Lilacs databases, and “mental health”, “students” and “race” in the PubMed database. The filters used were: articles in Portuguese and English, full text, published in the year 2015 until 2020. Results: After the search, a Brazilian study and 12 North Americans answered the proposed guiding question and were selected for analysis. Most studies (08) were quantitative cross-sectional, using questionnaires in the proposed investigation. In addition to these, a qualitative interpretive meta-synthesis was identified; a cross-sectional study based on semi-structured interviews; and three longitudinal studies. Conclusion: The rarity of articles that include the variable race in the analyzes of mental health among university students becomes evident in this research; this denotes neglect of the specificities faced by the black student due to racism. The perceived scarcity motivates further studies on the dimension of the problem and on possible solutions for inclusion and training of better professionals.